Ideal Construction of Collective Wealth Sharing - Muhammad Andri; Haris Budiman (Universitas Kuningan, 2021)
This article discusses the issue about collective wealth sharing. In principle of Islam does not regulate the detail of collective wealth sharing except according to syirkah, but in the Marriage Law that any wealth is obtained during the marriage period becomes joint wealth, regardless of who works or obtains the assets and in whose name, as long as the wealth is not an inheritance, gift or inheritance, and there is not marriage agreement in terms of joint ownership. With the problem of how the ideal construction of distribution wealth sharing for wife who has income. The research method uses normative juridical research with case and approach regulations . The results of this research proves that distribution wealth sharing for wife who works and does not forget the responsibilities and duties as a wife, then when a divorce occurs, the distribution of joint wealth can deviate from the law (Article 97 KHI) this is in accordance with the Supreme Court decision MA No. 266K / AG / 2010 with the wife's acquisition of 3/4 share, while the husband's remaining is 1/4 share. Meanwhile, in the decision of the Banjarnegara Religious Court Number 1372 / Pdt.G / 2011 / PA.Ba. In this verdict, a wife gets more share than the husband gets, with the husband's share being 2/5 and the wife 3/5 of the share. This decision provides a sense of justice, and this is an ideal construction in the distribution of collective wealth by considering the principle of balance.Keywords: Ideal Construction, Distribution, Joint Wealth,